Coast-Wide Nursery Contribution of New Recruits to the Population of Atlantic Menhaden. Issue 3 (3rd May 2016) - Anstead, Kristen A.; Schaffler, Jason J.; Jones, Cynthia M.
Abstract: The Atlantic Menhaden Brevoortia tyrannus is a coastal-spawning, estuarine-dependent clupeid that has economic and environmental value along the U.S. East Coast. Atlantic Menhaden spawn offshore and rely on circulation patterns in the ocean to deliver larvae to multiple estuarine nursery grounds for juvenile development before recruiting to the adult stock. Historical estimates of the Atlantic Menhaden nursery contribution by each of the major nurseries along the coast indicate that the Chesapeake Bay produces 69% of the recruits to the adult stock; yet, these estimates are over 20 years old and have never been quantitatively validated. We used otolith chemistry for three cohorts of age-1 Atlantic Menhaden to evaluate nursery contribution and provide updated recruitment rates for each of the nursery grounds for this species. Based on geochemical signatures and a quadratic discriminant function that assigned juveniles to their nursery grounds at nearly 90% accuracy, we classified age-1 menhaden of unknown nursery origin collected coastwide. We found that for the 2009–2011 year-classes, the contribution from Chesapeake Bay still dominates the proportion of age-1 recruits, but this contribution has declined to between 16% and 65% of that earlier estimate. Nursery grounds in New England as well as those found south of Chesapeake Bay have become more significant contributors of age-1 Atlantic Menhaden than previously expected. Received November 7, 2015; accepted January 26, 2016 Published online April 27, 2016